Combined Effects of Exercise and Vitamin D on Neuroinflammation, Blood-Brain Barrier Integrity, Oxidative Stress, and Cognitive Function in Nonpathological Mice - Kim, Taewan; Kim, Donghyun; Kim, Yoonhwan; Kim, Jeonghyeon; Kang, Seamon; Cho, Jinkyung (International neurourology journal, 2025)
Purpose: This study investigated whether the combined application of treadmill exercise and vitamin D injections exerts neuroprotective effects in nonpathological mice by enhancing cognitive function, regulating immune responses, preserving blood-brain barrier (BBB) integrity, and improving mitochondrial efficiency.Methods: Forty male C57BL/6 mice were randomly assigned to control, exercise (EX), vitamin D (VD), or combined treatment (EXVD) groups. After 20 weeks of intervention, behavioral, molecular, and cellular analyses were performed to assess cognitive function, immune responses, BBB integrity, oxidative stress, and mitochondrial efficiency.Results: The EXVD group demonstrated superior spatial learning and memory compared to the other groups. Vitamin D treatment significantly increased plasma interleukin-10 and tight junction protein levels, while exercise alone elevated hippocampal tumor necrosis factor-α. Combined treatment reduced astrocyte activation, maintained BBB integrity, and improved mitochondrial respiratory efficiency without increasing oxidative stress. Expression of antioxidant enzymes was decreased in the VD and EXVD groups, indicating improved redox balance.Conclusions: Treadmill exercise and vitamin D injections confer neuroprotective effects in nonpathological mice by enhancing cognition, reducing neuroinflammation, and improving both BBB integrity and mitochondrial function. These findings highlight the potential of nonpharmacological strategies to support brain health even in the absence of disease.